The Influence of Teacher Competence, Parental Attention, On Student Learning Motivation at Vocational Schools in Makassar - Ichsan Kamil A Hafid; Darmawang; Mantasia (Universitas Nahdatul Ulama Surabaya, 2025)
Vocational education plays a pivotal role in preparing competent graduates; however, students’ success is highly dependent on their learning motivation. Teacher competence and parental support are widely recognized as key factors that shape this motivation. Therefore, this study aims to examine the influence of pedagogical competence, professional competence, and parental attention on learning motivation among Class XI students specializing in Electrical Installation Engineering at State Vocational Schools in Makassar City. This research employed a quantitative approach using an ex post facto design. The population consisted of 279 students, from which a sample of 164 respondents was selected through proportional random sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics and multiple linear regression techniques. The findings indicate that pedagogical competence, professional competence, and parental attention each have a positive and significant partial effect on learning motivation, as well as a significant simultaneous effect. Together, these three variables contributed 18.5% to the variance in student learning motivation, with professional competence emerging as the strongest predictor. The study concludes that enhancing teacher quality and strengthening parental engagement are critical for improving learning motivation and, consequently, student success in vocational education. It is recommended that schools provide continuous professional development opportunities for teachers and promote closer collaboration with parents to cultivate a more supportive learning environment